29P-D-6 虚言発言時の心拍変動解析とVisual Analog Scaleによる主観評価との相関(主観評価,一般講演) - 大井, 理紗; 秋田谷, 研人; 松本, 有二; 高橋, 達矢; 小川, 勇人; 安形, 将史; 渡邉, 志 (バイオメディカル・ファジィ・システム学会大会講演論文集, 2011)
This paper discusses effects of telling a lie to the changes of the correlation between heart rate variability (HRV) analysis and psychological state evaluation using visual analog scale (VAS). The experiment employed 8 healthy subjects. The HRVs of the subjects are recorded when they tell a lie. And the HRVs are also recorded when they tell the truth. Furthermore, in order to investigate the mental tension, the subjects are required to answer the questionnaire on VAS, in both cases (when conducting the experiment and when not). The HRV data are analyzed by using FFT. The low frequency component (LF: 0.04 to 0.15Hz) and high, frequency component (HF: 0.15 to 0.40Hz) are obtained from the HRV power spectrum. The experiment result shows that VAS data are high when the subjects tell a lie, and there exists a liner relationship between LF/HF ratio and VAS data.